Hare - Carnell, Simon, 1962- (Animal (Reaktion Books), 2010)
"In times past reckoned to be the 'most lascivious and most melancholy' of mammals, the hare was also believed to never close its eyes, occasionally to grow horns, and to be able to change its gender. It was credited in early medicine with the most curative properties of any animal. But the hare is in fact as remarkable for its actual characteristics and behaviour as for the intriguing myths that have developed around it. In this book, Simon Carnell examines how the hare has been described, symbolized and depicted, as well as valued for its fur, flesh and exceptional speed."--Jacket